2013
DOI: 10.1111/inr.12007
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of diabetes empowerment questionnaire in Iranian people with type 2 diabetes

Abstract: The Diabetes Empowerment Questionnaire is a reliable and valid tool to assess patient empowerment in Iranian people with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 27 publications
2
33
0
5
Order By: Relevance
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen definitions (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) (Chart 1) and seven dimensions (9,14,(24)(25)(26)(27)(28) of empowerment (Chart 2), and 10 empowerment measures (9,13,24,(29)(30)(31)(32)(33)(34)(35) (Chart 3) were selected. The analysis showed that the concept of empowerment has been broadly used in the health sciences field, especially over the last 10 years.…”
Section: Resultsmentioning
confidence: 99%
“…Fotoukian et al, 2014 (14) Ouschan et al, 2000 (25) Salmon et al, 2004 (28) Gaining control Small et al, 2013 (9) Fotoukian et al, 2014 (14) Ouschan et al, 2000 (25) Aujoulat et al, 2008 (26) Oh et al, 2012 (27) Salmon et al, 2004 (28) Knowledge acquisition Aghili et al, 2013 (24) Ouschan et al, 2000 (25) Aujoulat et al, 2008 (26) Coping skills …”
Section: Definition and Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…유방암 [8,23,27], 여성성 수용 [28], 자기통제 [6,8,22,27,28], 자기효능 [17,19,23,27], 자기결정 [8,17,23] 으로 하였고, 이는 유방암으로 인해 손상된 여성성을 긍정적으로 회 복하고 목적 달성을 위하여 자율적인 선택을 시행하며 자신의 삶을 조절하고자 하는 주도적인 역량을 의미한다. 상호작용적 요인의 개 념적 지표는 가족 대인관계 [5,10], 동료 대인관계 [7,10,23,27], 의료 인 대인관계 [7,9,18,20,21] Figure 2). …”
unclassified